Assessing factors that influence graduate student burnout in health professions education and identifying recommendations to support their well-being - Jacqueline M. Zeeman; Emili B. Anderson; Isabel C. Matt; Michael B. Jarstfer; Suzanne C. Harris (PLoS ONE, 2025)
Background While well-being has become increasingly important in graduate education, limited information exists regarding factors contributing towards burnout and well-being in Pharmaceutical Sciences Doctor of Philosophy (PhD) students. This exploratory story aimed to identify factors influencing well-being and burnout in these students as well as identify recommendations to support their well-being. Methods A two-stage sampling approach was used: (1) purpose sample of Pharmaceutical Sciences PhD students at a public university were invited to participate in a semi-structured focus group or interview to explore factors contributing to PhD student burnout and well-being as well as solicit suggestions for strategies to improve their well-being; (2) Stratified sampling was used to assign participants into focus groups by All-But-Dissertation (ABD) status (i.e., pre-ABD candidates, ABD candidates) to explore experiences that may be unique to these students. Inductive coding and thematic analysis were used. Results Six PhD candidates participated in three sessions: three Pre-ABD candidates in one focus group, two ABD candidates in one focus group, and one ABD candidate in one interview. Participants identified relationships and aspects of curriculum and research (i.e., program design, completing milestones) as factors influencing their well-being. Factors influencing participants’ burnout included curriculum and research stressors (e.g., cumulative exams, competing academic and research responsibilities), working overtime, unrealistic expectations, lack of work life balance, and financial burden. While relationships and curriculum and research were factors in both subgroups, unique aspects within these themes emerged between Pre-ABD and ABD participants. Participant recommendations to foster PhD student well-being included improving financial support and encouraging PhD connections. Conclusions This study advances knowledge on factors influencing PhD student well-being and burnout, providing suggestions to improve their well-being. Findings highlight curriculum and research factors as well as relationship dynamics influence graduate student burnout and well-being. Findings contribute to broader conversations aimed to support student wellness and reduce burnout in higher education, informing the academy of focused areas and strategies to improve PhD student well-being.